2016
DOI: 10.5455/ajvs.235400
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sperm Concentration and Site of Insemination on Conception Rate of Rabbits

Abstract: A total number of 16 mature bucks and 190 monoparous does' of New Zealand White rabbits were used in this work. The aim of this study was to evaluate some reproductive traits and semen quality. The traits measured were semen-ejaculate; sperm motility; sperm-cell concentration; the percentages of live spermatozoa; total-sperm abnormalities and acrosomal damages by conventional technique. Pooled semen sample was divided into two homogeneous parts then diluted with glucose yolk citrate diluents. The dilution rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In the literature, there are contradictory results regarding the number of sperm cells required per insemination in rabbits. Rriad et al, (2016) reported that increasing the sperm number used per insemination from 16.8 × 10 6 to 33.5 × 10 6 increased the pregnancy rate significantly. Similarly, Alvariño et al, (1996) stated that reducing the sperm number from 26 × 10 6 to 20 × 10 6 resulted in reduced pregnancy rates and that further reduction the sperm number to 14 × 10 6 per insemination also reduced the litter size.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are contradictory results regarding the number of sperm cells required per insemination in rabbits. Rriad et al, (2016) reported that increasing the sperm number used per insemination from 16.8 × 10 6 to 33.5 × 10 6 increased the pregnancy rate significantly. Similarly, Alvariño et al, (1996) stated that reducing the sperm number from 26 × 10 6 to 20 × 10 6 resulted in reduced pregnancy rates and that further reduction the sperm number to 14 × 10 6 per insemination also reduced the litter size.…”
Section: Discussionmentioning
confidence: 99%
“…According to Eschborn (1985), AI was performed using disposable plastic curved pipettes (Imporvet, S.A.). Does were inseminated with 1 mL of frozen–thawed semen (75 × 10 6 ) and deposited deep into the vagina (12 cm beyond the pelvic brim; Rriad et al., 2016). At days 10–12 post‐insemination, pregnancy was established by abdominal palpation to calculate the conception rate (number of pregnant does/number of inseminated does × 100).…”
Section: Methodsmentioning
confidence: 99%
“…It showed to be 0.5 ml of diluted fresh semen containing about 1.6 × 10 6 motile sperm (Chen et al 1989), more than 50 x 10 6 motile sperm (Seleem 2003), diluted 1:3 with 80-100×10 6 spermatozoa/ml (López-Gatius et al 2005), diluted 1:5 with 6 x 10 6 spermatozoa/ ml (Lavara et al 2005), diluted 1:6 with 60 x 10 6 spermatozoa/ml (Zeidan et al 2008). Rowida et al (2016) found that increasing the number of spermatozoa (45.04×10 6 / 0.5 ml) in dilution rate 1:5 and deposit inter vagina at 12 cm improved conception and kindling rates while litter size was not affected. J Anim Behav Biometeorol (2020) 8:120-130 Sperm numbers required for optimal fertility can be reduced in case of deep vaginal-cervical insemination as an important factor in commercial AI of rabbits (Tantasuparuk et al 2011).…”
Section: Semen Quality and Site Of Inseminationmentioning
confidence: 96%
“…Therefore, one of the most important factors associated with high fertility with AI is the site of semen deposition inside the doe vagina. There is a difference in the length of the rabbit vagina which was showed to be 10.0 cm (Frandson 1981), 20.8 cm (Morrell 1995), 14 to 19 cm long (Rebollar 2011), and 14.5 to 19.5 cm (Rowida et al 2016). These differences may be due to strain and age of rabbit does.…”
Section: Semen Quality and Site Of Inseminationmentioning
confidence: 99%
See 1 more Smart Citation